The Role of Behavioral Empowerment and Smart Technologies in Enhancing Investor Decision-Making and Portfolio Optimization in the Iranian Capital Market - Eskandari, Mahboubeh; Mohseni, Abdolreza; Ghasemi, Mostafa (Business, Marketing, and Finance Open, 2026)
This study aimed to examine how cognitive–behavioral empowerment, smart FinTech applications, and behavior–finance integration jointly influence investor decision-making and portfolio optimization among individual investors in the Iranian capital market. The research employed a mixed-method descriptive–survey design. In the qualitative phase, semi-structured interviews were conducted with ten experts in finance, investment psychology, and information technology to extract key components of behavioral empowerment and technological integration. In the quantitative phase, data were collected from 384 individual investors of the Tehran Stock Exchange using a researcher-developed questionnaire validated through content analysis and pilot testing. Data analysis was performed using SPSS 26 and AMOS 24 through confirmatory factor analysis and structural equation modeling to test the hypothesized relationships among cognitive–behavioral empowerment, smart FinTech application, behavior–finance integration, and portfolio optimization. The structural equation model demonstrated excellent fit indices (CFI = 0.956, TLI = 0.948, RMSEA = 0.041). Results showed that all three constructs exerted positive and significant effects on portfolio optimization (p < 0.001). Smart FinTech application exhibited the strongest standardized effect (β = 0.41), followed by cognitive–behavioral empowerment (β = 0.33) and behavior–finance integration (β = 0.29). The model explained 64 percent of the variance in portfolio optimization (R² = 0.64), indicating strong explanatory power. These results highlight that combining behavioral empowerment with technological innovation enhances decision quality, reduces bias, and improves portfolio performance. The study concludes that empowering investors psychologically and cognitively, alongside adopting intelligent financial technologies and integrating behavioral analytics into financial models, significantly optimizes investment portfolios. This integrative approach provides a holistic framework for improving decision-making efficiency and portfolio outcomes in emerging markets such as Iran.